Case Report: A novel TP53 mutation in a patient with quadruple wild-type gastrointestinal stromal tumor - Chen, Yuhong; Chen, Junyong; Long, Liansheng; Han, Leng; Mi, Xiaohui; Song, Yanfang; Cheng, Huanqing; Zhang, Yanrui; Cheng, Liyang (Frontiers in Oncology, 2023)
In this report, we present a case study of a 64-year-old female who was diagnosed with gastrointestinal stromal tumors (GISTs) and subsequently developed liver metastases despite undergoing radical resection. Next-generation sequencing (NGS) assays indicated that the tumor lacked KIT/PDGFRA/SDH/RAS-P (RAS pathways, RAS-P) mutations, thereby classifying this patient as quadruple WT GIST (qGIST). Treatment with imatinib was initiated, and after 2.5 months, recurrence of the tumor and multiple metastases around the surgical site were observed. Consequently, the patient was switched to sunitinib treatment and responded well. Although she responded well to sunitinib, the patient died of tumor dissemination within 4 months. This case study highlights the potential efficacy of imatinib and the VEGFR-TKI sunitinib in treating qGIST patients harboring a TP53 missense mutation.